2017
DOI: 10.3390/inorganics5030053
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Substituent Effect on the Spin-Transition Temperature in Spin-Crossover Fe(III) Compounds Bearing Salicylaldehyde 2-Pyridyl Hydrazone-Type Ligands and Dicarboxylic Acids

Abstract: Abstract:Four TPA) (2-Br) (HL1 = 4-chloro-2-nitro-6-(1-(2-(pyridine-2-yl)hydrazono)ethyl)phenolate; HL2 = 4-bromo-2-nitro-6-(1-(2-(pyridine-2-yl)hydrazono)ethyl)phenolate; HCl 4 TPA = 2,3,5,6-tetrachloro-4-carboxybenzoate; and HBr 4 TPA = 2,3,5,6-tetrabromo-4-carboxybenzoate), were synthesized to investigate the halogen substituent change effect in salicylaldehyde 2-pyridyl hydrazone-type ligands and dicarboxylic acids in SCO complexes to the spin-transition temperature. Crystal structure analyses showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The additional presence of hydrogen bonding and cation-π interactions allow the 2D network structure to accommodate the geometric changes around the metal during SCO. Sato et al described the synthesis [88] of four Fe(III) SCO compounds [Fe(L9) 2 ] + , with salicylaldehyde 2-pyridyl hydrazone-type ligands (L9, X = Cl, Br) and dicarboxylic acid monoanions (tetrachloroterephtalic and tetrabromoterephtalic acids) to investigate the influence of the halogen in the spin-transition temperature of SCO complexes. The crystal structures showed a 1D chain formed by the OH···O charge assisted hydrogen bonds between anions, which also form NH···O hydrogen bonds with the cations.…”
Section: Methodsmentioning
confidence: 99%
“…The additional presence of hydrogen bonding and cation-π interactions allow the 2D network structure to accommodate the geometric changes around the metal during SCO. Sato et al described the synthesis [88] of four Fe(III) SCO compounds [Fe(L9) 2 ] + , with salicylaldehyde 2-pyridyl hydrazone-type ligands (L9, X = Cl, Br) and dicarboxylic acid monoanions (tetrachloroterephtalic and tetrabromoterephtalic acids) to investigate the influence of the halogen in the spin-transition temperature of SCO complexes. The crystal structures showed a 1D chain formed by the OH···O charge assisted hydrogen bonds between anions, which also form NH···O hydrogen bonds with the cations.…”
Section: Methodsmentioning
confidence: 99%
“…The most essential need, namely RT operation, is achievable by controlling the spin transition temperature (T 1/2 ) . Thus, the various molecular design and modifications have been reported for the precise tuning of T 1/2 [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Phonsri and co-workers [13] describe the ethoxy substitution effect on homoleptic and heteroleptic Fe(III) SCO systems and find that the steric effect leads to less cooperative SCO conversions. Nakanishi and co-workers [14] investigate the halogen substitution effect on both the ligand and counter-anion for an Fe(III) SCO complex. They were successful at isolating and characterizing four isostructural SCO complexes and found that the substitution of the ligand may result in an inner electronic effect, whereas substitution of the counter-anion may create an outer chemical pressure effect.…”
mentioning
confidence: 99%